Service infrastructure sharing of resettlers and host communities a case study of the Kasiglahan Vilage 3 (KV-3) Summerfield Subdivision in Trece Martires, Cavite - Marcelo, Rosalyn-Frances Osorio (2007)
This study aims to provide some ideas for resettlement planning, particularly in the aspect of integrating resettlers and hosts through service infrastructure sharing...
"November 2007."
Thesis (M.A. Urban & Regional Planning)--University of the Philippines Diliman.
Keywords: Relocation (Housing -- Philippines -- Trece Martires (Cavite) -- Cases studies